PRICE STABILIZATION AND IPO UNDERPRICING: AN EMPIRICAL STUDY IN THE INDONESIAN STOCK EXCHANGE - Husnan, Suad; Hanafi, Mamduh M.; Munandar, Muhammad (Journal of Indonesian Economy and Business, 2014)
We attempt to investigate IPO underpricing and stabilization activities. We find IPOunderpricing of around 25% in the Indonesia market. Return distribution for the first 30-tradingdays shows a positive skew, the distribution becomes closer to normality as the periodlengthens. We then develop and test five algorithms to detect IPO intervention. An importantgoal of this paper is to develop an algorithm that will be able to detect IPO intervention usingpublic data. We find that the number of closing prices that are equal to the offer prices and theskewness of the IPO return in the first 30-trading days are the âbestâ stabilization measures.Having found âthe best measuresâ, then we investigate under what conditions IPO interventionis more intensive. We find that underwriters tend to stabilize more on more expensive IPOs.Keywords: IPO, Indonesia, underpricing, stabilization